Penerapan Aplikasi ARBE Berbasis Inkuiri Pada Praktikum Larutan Penyangga Untuk Meningkatkan Kemampuan Reprsentasi Mahasiswa - solihah, fitriani; sari; Irwansyah, Ferli Septi; Farida, Ida (Jurnal Riset Pendidikan Kimia (JRPK), 2024)
This study aims to describe student activities, analyze and analyze the increase in student representation abilities after the application of guided inquiry-based ARBE applications in buffer solution practicum. The research method used was a pre-experimental design with one group pretest-posttest. The subjects of thisstudy were second semester students of the chemistry education study program at UIN Sunan Gunung Djati Bandung with a total of 33 students. The instruments used were observation sheets of student activities, worksheets, and pretest posttest questions. The resultsshowed thatstudent activitywas 91.8% with a very good interpretation. The increase in studentrepresentation ability after implementing the guided inquiry-based ARBE application in the buffer solution practicum to improve student representation ability was classified as high with a gain value of 0.72. Based on the t-test, a significance value of 0.000 <0.05 means that H0 isrejected and Ha is accepted. This shows that the implementation of the guided inquiry-based ARBE application in the buffer solution practicum was able to improve students' representation abilities